Soil Quality in Land Suitability Analysis of Coffee Agroforestry in Patokpicis Village, Wajak District, Malang Regency - Affan, Muhammad; Zayadi, Hasan (Directorate of Research and Community Services, 2024)
Patokpicis is one of the villages in Wajak District, Malang Regency, which also develops agriculture and agroforestry, one of which is Coffee agroforestry. For a particular land use, a comparison must be made between the suitability of the land and the requirements of the land suitability level. The purpose of this study was to analyze the suitability of Argoforesty coffee agroforestry in Patokpicis village, Wajak District, Malang Regency. This research was conducted in February-July 2023. Furthermore, using qualitative descriptive methods, the object of this practice is land use data. The research results show that all sub-villages have good soil texture for the growth of coffee plants, with ideal soil pH and stable air temperature. Although there are some environmental factors that are not ideal, such as slightly high soil pH and somewhat high air temperature, the soil in the area still has good potential to support the growth of coffee plants. The research results show that Patokpicis and Bangsri hamlets are included in hamlets that have land suitability classes S1 and S2, while Klakah and Sumbersuko hamlets are included in the S1, S2, and N categories for the 4 soil characteristics analyzed.